An Analysis of the Increasing Divorce Rate in Tlogo Village, Tretep District, Temanggung Regency - Zaenal Arifin; Muhammed Zaki Tamami; Alifka Nur Ikhsan (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2026)
This study is motivated by the increasing divorce rate in Tlogo Village, Tretep District, Temanggung Regency, Indonesia, where marital dissolution has become a growing social concern. Divorce is influenced by various interrelated factors that undermine marital stability and family cohesion. This study aims to analyze the factors contributing to the rising divorce rate and to examine these factors from the perspective of Islamic law. Employing a qualitative research design with an empirical juridical approach, the study collected data through in-depth interviews, document analysis, and a literature review. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the rising divorce rate is primarily driven by economic hardship, emotional and psychological immaturity of spouses, prolonged marital conflicts, extramarital affairs, long-term separation, and domestic violence. These factors hinder the realization of the fundamental objectives of marriage, namely establishing a harmonious, stable, and prosperous family. From the perspective of Islamic law, divorce is recognized as a lawful but exceptional remedy when marital relationships result in persistent harm (mafsadah) and reconciliation is no longer attainable. Consequently, divorce is regarded as a legitimate legal mechanism to prevent greater harm and to preserve the welfare (maslahah) of both spouses